Evaluation study of plant rice fields some strains sub in production center Jailolo - Tri Mulya Hartati (Jurnal Agrivet, 2012)
To ensure the fulfillment of quality seed varieties ongoing basis in order to support increased production and productivity of rice plants, the use of quality seeds of improved varieties to suit every taste quality of farmers / seed users is worth noting. The new variety is declared superior and deserve to be disseminated if it has been released officially by the government. One of the requirements in the proposing release varieties are strains / mutants / hybrids / clones that have made adaptations proposed release of varieties, it is intended to determine the production potential and the ability to adapt to various environments, and it is known that environmental conditions appropriate notice of its development. Thus, the objectives of the adaptive test is to determine the production potential, agronomic characteristics and advantages of the strain / mutant / hybrid / clone in adjusting to the growth environment. This study aimed to evaluate multiple strains of rice paddy to the state of the environment in the production center of the village of Hoku-Hoku Kie, District Jailolo-West Halmahera district. This research used Randomized Block Design (RBD) a single factor using 7 strains are: OBS 1711/PSJ, OBS 1712/PSJ, OBS 1713/PSJ, OBS 1714/PSJ, OBS 1718/PSJ, OBS 1719/PSJ, OBS 1720/PSJ , and 3 varieties for comparison, namely Cimelati, Ciherang, and IR 64. The results demonstrate the ability of adaptation to the environment from several strains tested, strain OBS 1718/PSJ a strain that is able to adapt to the environment in Production Centers Hoku - Hoku Kie West Halmahera District JailoloKeywords: rice strain, environmental adaptation